Motyw "torcular Christi" i jego reminiscencje w średniowiecznej poezji liturgicznej - Gacia, Tadeusz (Vox Patrum, 2024)
The study presents reminiscences of the torcular Christi motif in the liturgical poetry of the Middle Ages against the background of evidence of its presence in the writings of the Fathers of the Church and authors of later centuries. The source of the motif is the text of the Book of Isaiah 63:1-3, referred to Christ as an allegory. The grape is Christ, and the winepress is His cross - torcular Christi. Since late antiquity, the text of Isaiah was read at Mass on Holy Wednesday and was part of the breviary office on the Friday after the third Sunday of Lent. The image of torcular Christi became permanent in the consciousness of the faithful and went beyond the liturgy - also into the world of art and poetry. The article refers to eleven poetic works which contain reminiscences of the motif of the pressing plant to varying degrees (in whole or in some fragments). These are texts by Peter Abelard, Peter the Venerable - Abbot of Cluny, Peter Damiani, Philip the Chancellor, Adam of Saint Victor and anonymous authors. The annex to the study contains the original text and the author’s translation into Polish of the commented source texts.